BIAS GENDER: MASALAH UTAMA DALAM INTERPRETASI ARKEOLOGI - Mimi Savitri (Humaniora, 2007)
Gender bias is an important theme in Gender Archaeology. It is influenced by modern people thinking and it has influenced archaeological interpretation for a long time. As a result, archaeological interpretation of past society is not objective. This problem should be solved to reach an objective interpretation of people’s life in the past. The author argues that gender bias in archaeology can be solved by actively criticizing androcentrism and paying more attention to men and women’s relationship in the past.